Evaluating for Pseudoprogression in Colorectal and Pancreatic Tumors Treated With Immunotherapy. Issue 6 (July 2018) - Parseghian, Christine M.; Patnana, Madhavi; Bhosale, Priya; Hess, Kenneth R.; Shih, Ya-Chen Tina; Kim, Bumyang; Kopetz, Scott; Overman, Michael J.; Varadhachary, Gauri R.; Javle, Milind; Naing, Aung; Piha-Paul, Sarina; et al.
Abstract : Pseudoprogression has been observed in patients with various tumor types treated with immunotherapy. However, the frequency of pseudoprogression is unknown in gastrointestinal malignancies. Metastatic colorectal cancer (mCRC) and advanced pancreatic ductal adenocarcinoma (PDAC) patients who progressed on treatment with immunotherapy beyond RECIST version 1.1 criteria were analyzed. Degree of progression, tumor markers, time to progression, overall survival, Eastern Cooperative Oncology Group Performance Status (ECOG PS), and costs were analyzed for patients treated beyond progression (TBP) and not treated beyond progression. Fifty-nine of 159 (37%) patients with mCRC or PDAC were TBP (31 mCRC, 28 PDAC). Fifty-four of 59 (92%) patients were microsatellite stable. Zero of these 59 patients with initial treatment beyond progression demonstrated subsequent radiographic tumor shrinkage at a median 42 days from first scan documenting progression. A pseudoprogression rate of >6% could be excluded with 95% confidence. Compared with baseline, median growth on the first and second scan that showed progression was 29.8% and 43%, respectively. In those not treated beyond progression, median growth at first restaging was 31.2%. The trend in change in tumor size positively correlated with the trend in tumor markers in all patients TBP. Fifteen patients (25%) experienced grade 3/4 adverse events by continuing treatment beyond progression, whereas 19 (32%) experienced deterioration in ECOG PS. Pseudoprogression was not seen in microsatellite stable patients with mCRC or PDAC treated with immunotherapy. Changes in tumor markers correlated with changes in tumor volume. This data may help inform future treatment decisions and/or trial design in patients with mCRC or advanced PDAC treated with immunotherapy. Abstract : Supplemental Digital Content is available in the text.